Surgical management of head and neck squamous cell carcinoma metastatic to the parotid gland - Gontarz, Michał; Urbańska, Marta; Bargiel, Jakub; Gąsiorowski, Krzysztof; Marecik, Tomasz; Wyszyńska-Pawelec, Grażyna (Frontiers in Oncology, 2025)
The parotid gland includes lymph nodes that may contain metastasis from the head and neck region as well as distant metastasis or metastasis from carcinoma/melanoma of an unknown primary (CUP/MUP). This study aimed to review the current literature to evaluate the role of surgical management of head and neck squamous cell carcinoma (HNSCC). A narrative review of the English language literature available in the PubMed and Embase databases from January 2010 to December 2024 was conducted to identify treatment methods and follow-up data for HNSCC metastatic to the parotid gland. This study provides a detailed overview of the histological and diagnostic imaging characteristics as well as the surgical and non-surgical procedures employed in the management of HNSCC metastases to the parotid gland. Furthermore, the management of CUP is outlined. The extent of the parotidectomy and concomitant neck dissection remains a topic of ongoing debate. The flow chart presented in this study may assist in decision-making regarding surgical treatment. Given that locoregional recurrence is the primary cause of mortality in HNSCC, surgical treatment is likely to be the most effective means of achieving a favorable outcome.